2018
DOI: 10.3390/nu10121881
|View full text |Cite
|
Sign up to set email alerts
|

Are Gluten-Free Diets More Nutritious? An Evaluation of Self-Selected and Recommended Gluten-Free and Gluten-Containing Dietary Patterns

Abstract: Gluten-free (GF) eating patterns are frequently perceived to be healthier than gluten-containing (GC) ones, but there has been very little research to evaluate this viewpoint. The effect of GF eating patterns on dietary composition was assessed using two independent approaches. One approach compared macronutrients and typical shortfall nutrients between MyPlate example menus developed with either GC or equivalent GF foods. In this analysis, the GF menus were significantly lower in protein, magnesium, potassium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 24 publications
1
55
0
4
Order By: Relevance
“…GF products are made with high amounts of fat and sugar to achieve a texture resembling the typical and unique wheat viscoelastic properties [18,19]. Fat ingredients are indeed useful in bakery products for the stabilization of gas bubbles and the reduction of kneading resistance and swelling of starch granules [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GF products are made with high amounts of fat and sugar to achieve a texture resembling the typical and unique wheat viscoelastic properties [18,19]. Fat ingredients are indeed useful in bakery products for the stabilization of gas bubbles and the reduction of kneading resistance and swelling of starch granules [31].…”
Section: Discussionmentioning
confidence: 99%
“…Celiac patients may also be at risk of iron and folate deficiencies [17]. Some authors state that nutritional deficiencies in CD patients may be due to GF products, which are made with highly refined flours and high amounts of fat and sugar to achieve a texture resembling the typical and unique viscoelastic properties of wheat [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The suggestion that children on a GFD may not be taking adequate fiber intake results from observations indicating that gluten-free foods are often composed of low-fiber starches and refined flours [39]. The considerably lower fiber level in GF dietary patterns that include lower grain consumption is thus likely to hamper the prevention of non-communicable diseases such as obesity, type 2 diabetes, and cardiovascular disease [41].…”
Section: Macronutrientsmentioning
confidence: 99%
“…The use of buckwheat flour has increased considerably due to the recognition by the consumers of its potential health benefits, presenting an increased commercial interest in the gluten-free market [14]. Nevertheless, several studies showed that many gluten-free foods are deficient in dietary fiber, micronutrients and protein [15,16]. Therefore, the combination of gluten-free flours with other health-promoting factors, such as proteins and bioactive peptides, has also received increased attention as potential functional foods [17].…”
Section: Introductionmentioning
confidence: 99%